Cover Feature: Formation, Structure, and Composition of Methylaluminoxane (ChemPhysChem 23/2017). Issue 23 (6th December 2017) - Linnolahti, Mikko; Collins, Scott
Abstract : The Cover Feature illustrates the relative abundancies and structural transitions of methylaluminoxane (MAO) oligomers as a function of molecular weight. Cage‐like structures dominate the MAO mixture, the peak composition having a tubular structure and a molecular weight of 1360 g mol −1 . The MAOs play an important role in catalytic preparation of polyolefins. More information can be found in the Full Paper by M. Linnolahti and S. Collins onpage 3369 in Issue 23, 2017 (DOI:10.1002/cphc.201700827 ).